The inflammasome signaling axis in thrombi from STEMI patients is related to degree of myocardial injury. (25th November 2020) - Nordeng, J; Helseth, R; Aakra, S; Hoffman, P; Schandiz, H; Roald, B; Bendz, B; Arnesen, H; Solheim, S; Seljeflot, I
Abstract: Background: The NLRP3-inflammasome and the IL-6-pathways, i.e. the inflammasome signaling axis, seems to be central mechanisms in the inflammatory response related to myocardial reperfusion injury after revascularization. The beneficial results shown by treating MI-patients with canakunimab, an antibody blocking IL1-β, in the CANTOS trial*, and by treatment of NSTEMI patients with the IL6-receptor antagonist tocilizumab**, are looked upon as proof of concept for inflammasome inhibition. Purpose: To study whether genes encoding inflammasome-related proteins are present in coronary thrombi and in circulating cells from STEMI patients, and whether these are related to the degree of myocardial injury as measured by troponin T, and time from symptoms to PCI. Methods: Intracoronary thrombi were aspirated from 33 patients with STEMI treated with primary PCI. The thrombi were snap-frozen in RNA-later solution for gene expression analyses. Peripheral blood samples with Pax-gene tubes were drawn at end of the PCI-procedure. mRNA of NLRP3, caspase1, IL1-β, IL18, IL6, IL6-receptor (IL6-R) and gp130 were isolated from the thrombi and leukocytes in peripheral blood, and relatively quantified by RT PCR. Peak troponin was collected from clinical records. Results: Genes coding for the 7 different markers were present in 76–100% of the thrombi. The expression of NLRP3 in thrombi significantly correlated to peak troponin T (r=0.468, p=0.024). Dividing peak troponin T values into quartiles, the median value of NLRP3 mRNA in Q4 was 2.0-fold higher compared to Q1–3 (p=0.012). Peak troponin T also correlated with the expression in circulating leukocytes of NLRP3 (r=0.420, p=0.0149) and IL1-β (r=0.394, p=0.023), and borderline to caspase1 (r=0.321, p=0.069) and IL18 (r=0.310, p=0.079). IL6-R expression in thrombi correlated significantly to peak troponin T (r=0.434, p=0.019), with a 2.5-fold higher median level in Q4 vs Q1–3 of troponin T (p=0.017). gp130 expression in thrombi correlated inversely with peak troponin T (r=−0.398, p=0.050), as did IL6-R expression in circulating leukocytes (r=−0.421, p=0.015). There were no significant correlations between genes expressed in the thrombi and time from symptom to PCI (median 152 minutes), whereas genes for IL6 in circulating leukocytes correlated inversely (r=−0.385, p=0.027). Conclusion: The inflammasome signaling pathway was actively regulated in coronary thrombi and in circulating leukocytes from patients with STEMI. Genes encoding NLRP3 and IL6-R were increasingly expressed in thrombi from patients with increased myocardial damage, measured by troponin T, supporting the beneficial effects of medically targeting this pathway. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Stein Erik Hagens Foundation for Clinical Heart Research